Fluorescein-guided surgery for the resection of pilocytic astrocytomas: A multicentric retrospective study - Falco, Jacopo; Höhne, Julius; Broggi, Morgan; Rubiu, Emanuele; Restelli, Francesco; Vetrano, Ignazio G.; Schiariti, Marco; Mazzapicchi, Elio; Bonomo, Giulio; Ferroli, Paolo; Schebesch, Karl-Michael; Acerbi, Francesco (Frontiers in Oncology, 2022)
Objective: Pilocytic astrocytomas (PAs) are relatively benign tumors, usually enhancing on post-contrast MRI and often characterized by a mural nodule within a cystic component. Surgical resection represents the mainstay of treatment, and extent of resection (EOR) is associated with improved survival. In this study, we analyzed the effect of sodium fluorescein (SF) on visualization and resection of these circumscribed astrocytic gliomas. Methods: Surgical database at two neurosurgical departments (Fondazione IRCCS Istituto Neurologico Carlo Besta, Milan, Italy – Department of Neurosurgery, University Medical Center Regensburg, Regensburg, Germany) were retrospectively reviewed to identify the cohort of patients with pilocytic astrocytoma who had undergone fluorescein-guided tumor resection at any of the centers between March 2016 and February 2022. SF was intravenously injected (5mg/kg) immediately after induction of general anesthesia. Tumors were removed using a microsurgical technique with the YELLOW 560 filter (Carl Zeiss Meditec, Oberkochen, Germany). Results: Forty-four patients (25 males and 19 females; 26 pediatric patients, mean age 9.77 years, range 2 to 17 years and 18 adult patients, mean age 34.39 years, range 18 to 58 years) underwent fluorescein-guided surgery. No side effects related to SF occurred. In all tumors, contrast enhancement on preoperative MRI correlated with intense, heterogeneous yellow fluorescence with bright fluorescent cystic fluid. Fluorescein was considered helpful in distinguishing tumors from viable tissue in all cases except three patients due to faint fluorescein enhancement. Biopsy was intended in two operations, and partial resection was intended in three operations. Gross total resection was achieved in 24 cases out of 39 patients scheduled for tumor removal (61.54%), in 5 cases a minimal residual volume was highlighted by postoperative MRI despite the intraoperative subjective evaluation of complete tumor removal (12.82%); in other 10 cases, the resection was subtotal with fluorescent residual spots to avoid neurological worsening (25.64%). Conclusions: The use of SF is a valuable method for safe fluorescence-guided tumor resection. Our data showed a positive effect of fluorescein-guided surgery on intraoperative visualization during resection of PAs suggesting a possible role in improving the extent of resection of these lesions.